Conflicts, Problems and Solutions in the Family - A.Sh. Usmanov; O.P. Jiyanov; Taylanova Shohida Zaynievna; Nurgatina, Olga Nikolaevna (Research Parks Publishers, 2021)
This article is devoted to the regulation of family relations, the prevention of family divorces, the protection of the rights and interests of not only the couple, but also minors, the reconciliation of families on the verge of divorce, the peaceful resolution of disputes